PENGARUH RASIO KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Namira Ufrida Rahmi; Gunawaty Gunawaty; Lamsahat Pangihutan Malau; Mulyani Hofni Br Sitepu (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The study was conducted to determine the effect of profitability, liquidity, leverage and firm size on the disclosure of Corporate Social Responsibility either partially or simultaneously. This study uses a quantitative descriptive approach, with the population being food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2017 to 2020. The sampling technique uses Probability Sample with purposive sampling method and obtains sample data of 9 companies and 36 sample data. Analysis of the data using SmartPLS software with the results of the study being that the variables of profitability, liquidity, leverage and company size did not affect the disclosure of Corporate Social Responsibility in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The value of the coefficient of determination is 46.5%. Hypothesis test obtained t arithmetic > t table or (9.139% > 0.985%). Thus H1,H2,H3 and H4 is rejected and Ho is accepted, meaning that there is no a significant influence of profitability, liquidity, leverage and firm size. Profitability, liquidity, leverage and firm size has no a significant effect on corporate social responsibility with the regression equation Y = -0,058X1 + 0,124X2 + 0.,428X3 – 0,08X4, The value of the coefficient of determination is 15,5% while the remaining 84,5% is influenced by other factors.